Nordic agriculture air and climate - Antman, Anne (TemaNord, 2015)
This report constitutes the main outputs of the project "Pathways to a Nordic food system that contributes to reduced emissions of greenhouse gases and air pollutants". The overall goals are to present the baseline data regarding the Nordic agricultural sector, its greenhouse gas and ammonia emissions, the regulatory framework and support systems, and conflicts of interest. The report aims to describe pathways to a Nordic food system that contributes to achieving the climate target of below 2 (or 1.5) degrees of warming and the air pollution target of zero exceedance of critical loads and critical levels regarding ammonia emissions. The Nordic region has diverse geological and climatic conditions that make certain types of agricultural production more vulnerable than others. The policy recommendations aim to serve as input to different policies at EU, Nordic and national level.